The Effect of the Extraordinary Control on the seizures of the Callao Port Terminal, 2020-2023 - Guevara Gómez, Johan Marcelino (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This research study examines the impact of Extraordinary Control Actions (ACE) on seizures at the Arnold Peter Møller-Maersk (APM) Terminals checkpoint. The methodology was quantitative, descriptive-correlational, and non-experimental. The population consisted of 577 monthly incident reports, and a non-probabilistic sample of 211 reports was selected. Data was collected using a data collection form. A Cronbach’s alpha of 81.9% was obtained for the reliability of the data collection form, which was validated using a pilot study of 15 reports. The results show that the ex-ante evaluation dimension is associated with seizures, with a Spearman’s rank correlation coefficient of 0.543 (p<0.05). The intermediate evaluation is associated with seizures, with a Spearman’s rank correlation coefficient of 0.874 (p<0.05), and the ex-post evaluation is associated with seizures, with a Spearman’s rank correlation coefficient of 0.408 (p<0.05). In conclusion, extraordinary controls are linked to seizures at the APM Terminals checkpoint in Callao. Thus, these control measures have significantly influenced the capacity to detect and retain illicit or irregular goods at the checkpoint, demonstrating the effectiveness of the controls.